Financing Energy Efficiency Measures for Residential Building Stock : Scaling Up Energy Efficiency in Buildings in the Western Balkans - Kalkum, Bernd (World Bank Group, Washington, DC, 2014)
Within the Western Balkans region, a secure energy supply is critical to sustaining economic growth. Currently, the region relies heavily on imported hydrocarbons and maintains high energy intensity relative to Gross Domestic Product, or GDP. This places a huge burden on companies, which require affordable and reliable infrastructure services to be competitive; the public sector, which spends significant budgetary resources on energy; and households, which have to pay a high portion of their income for energy services. As energy pricing is further rationalized, a higher burden will be placed on all sectors, especially poorer households. The residential sector is a significant energy consumer. Its share of total final energy consumption ranges from 28 percent to 32 percent (compared with the EU average of 27 percent). Fairly simple renovations such as insulation, heating system upgrades, and improvements to windows and lighting could reduce consumption in this sector by some 9 percent, with payback periods generally less than 8 years. Such improvements could help ease the impact of future tariff increases while helping reduce the region's projected energy supply and demand gap.